Deconstructing Contemporary Chinese Art - Gladston, Paul. author. aut Link
XX, 195 p. 70 illus., 57 illus. in color.
Keywords: The book presents a range of articles and discussions that offer critical insights into the development of contemporary Chinese art, both within China and internationally. It brings together selected writings, both published and unpublished, by Paul Gladston, one of the foremost international scholars on contemporary Chinese art. The articles are based on extensive first-hand research, much of which was carried out during an extended residence in China between 2005 and 2010. In contrast to many other writers on contemporary Chinese art, Gladston analyses his subject with specific reference to the concerns of critical theory. In his writings he consistently argues for a “polylogic” (multi-voiced) approach to research and analysis grounded in painstaking attention to local, regional and international conditions of artistic production, reception and display.